Meteorological Factors and the Transmissibility of Hand, Foot, and Mouth Disease in Xiamen City, China - Xu, Jingwen; Yang, Meng; Zhao, Zeyu; Wang, Mingzhai; Guo, Zhinan; Zhu, Yuanzhao; Rui, Jia; Wang, Yao; Liu, Xingchun; Lin, Shengnan; Luo, Li; Su, Yanhua; et al. (Frontiers in Medicine, 2021)
As an emerging infectious disease, the prevention and control of hand, foot, and mouth disease (HFMD) poses a great challenge to the development of public health in China. In this study, we aimed to explore the mechanism of the seasonal transmission characteristics of HFMD and to reveal the correlation and potential path between key meteorological factors and the transmissibility of HFMD. This is the first study to explore the relationship between meteorological factors and the transmissibility of the disease. A total of 43659 cases of HFMD were reported in Xiamen from 2014 to 2018. Combined with daily meteorological data such as average temperature, average relative humidity, average wind velocity, amount of precipitation, average air pressure, evaporation capacity, sunshine duration, a database of HFMD incidence and meteorological factors was established. In the early stage of our analysis, Spearman rank correlation was used to calculate the correlation between the various meteorological factors and the incidence of HFMD. After a lag adjustment and collinear diagnosis, we found that there was a high correlation between average temperature and the incidence of HFMD. On this basis, the effective reproduction number (Reff) of HFMD was used as an intermediate variable to further quantify the dynamic relationship between average temperature and Reff. The results showed that there was a temperature threshold for HFMD transmissibility. Because of the seasonal transmission characteristics of HFMD in Xiamen, the temperature threshold of HFMD transmissibility in spring and summer was 13.4℃–18.4℃ and in autumn and winter was 14.5℃–29.3℃. Our research has opened the ‘black box’ on the relationship between meteorological variables and HFMD in traditional epidemiology. Based on our findings, we suggest that the relevant epidemic prevention departments should pay close attention to the temperature changes in Xiamen and formulate prevention strategies timeously before the arrival of the high-risk period.